1989
DOI: 10.1046/j.1537-2995.1989.29689318444.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of human and chimpanzee Kell blood group systems

Abstract: Kell antigens on chimpanzee (Pan troglodytes) red cells were determined using specific human alloimmune and murine monoclonal antibodies. After avoidance of interspecies reactions, chimpanzee red cells were found to react with most Kell system antibodies. The chimpanzees had phenotypes similar to those of humans. The main difference was that all of 27 chimpanzee red cell samples tested were of the K:6, -7, phenotype, while in humans most are K:-6, 7. The most common chimpanzee Kell blood group phenotype was K:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Chimpanzee's red cells also carry KEL6 antigens [31] and RFLP analysis of DNA from a single chimpanzee, by digestion of PCR products with MnlI and DdeI, indicated that the chimpanzee had the same base substitutions as noted in KEL6/6 humans.…”
Section: Molecular Basis Of Kell Blood Group Phenotypesmentioning
confidence: 93%
“…Chimpanzee's red cells also carry KEL6 antigens [31] and RFLP analysis of DNA from a single chimpanzee, by digestion of PCR products with MnlI and DdeI, indicated that the chimpanzee had the same base substitutions as noted in KEL6/6 humans.…”
Section: Molecular Basis Of Kell Blood Group Phenotypesmentioning
confidence: 93%
“…It is a complex system containing at least 24 antigens (1, 2) residing on a 93,000-kDa glycoprotein that is surface-exposed, spans the erythrocyte membrane, and is attached to the underlying cytoskeleton (3,4). Kell glycoproteins contain =12% carbohydrate by weight, all of which are N-linked glycosides (5,6).…”
mentioning
confidence: 99%
“…One has to notice that this Mab was unreactive with chimpanzee RBCs. Although it was demonstrated that chimpanzee RBCs were agglutinated by mouse Mabs reacting with human Kell-related antigens [20], the macaque Mab P.Mac-l2/1F9 failed to react with any chimpanzee RBC sample.…”
Section: Pnmac-8b/2e4mentioning
confidence: 97%